Medical Records Preservation And Archiving In A Selected Family Medicine Setting Saudi Arabia In 2024 (The Review of Diabetic Studies, 2024)
Introduction:Medical records play an important role in the storage and recall of patient’s information, patient’s follow-up, research, teaching, public health policy making and as a medico-legal tool, but less emphasis has been placed on its role in health care delivery. The objective of the study was to appraise the methods of conservation and archiving of medical records in hospitals in SaudiaMethods: Descriptive research design was utilized. Setting It was conducted in the private and public family medicine clinics in Gaddah, Saudia Arabia  Study subjects: Medical record clerks, health information clerks, and other hospital employees in charge of medical record preservation made up our study population. Tools : One tool were utilized to fulfill this study objectives, it was developed by the researchers Results: The results showed that 77.2% of participants did not know about the document life cycle or archival techniques. Lack of storage space 109 (80.1%), excessive humidity 100 (71.5%), dust 99 (72.8%), pest degradation 91 (61.9%), natural disaster 51 (37.5%), theft 44 (32.4%), computer virus attack 10 (7.4%), physical damage 84 (61.8%), and institution-specific lack of archiving policies 83 (61%). Overall, 52 participants (38.0%) prefer digital archiving, 11 participants (8.1%) choose paper exclusively, and 75 participants (53.7%) prefer both computer and paper archiving. 89.7% expressed dissatisfaction with their structure/service's technological conservation and archiving capabilities.Conclusion:The main challenges are summed up as follows: inadequate storage space (80.1%), a shortage of skilled workers to administer the medical file , and high humidity , which deteriorates medical data.  Half of participants support the simultaneous use of the two forms of medical record preservation, whereas the majority of participants express a negative opinion of the technological level of storage and archiving in the department or structure.